Hooking pattern, injury type and post-release survival of Genetically Improved Farmed Tilapia (GIFT) caught by circle and ‘J’hooks in recreational fishing - Jha, Paras Nath; Thomas, Saly N.; Madhu, V. R. (Indian Journal of Fisheries, 2020)
Recreational fishing by angling is practised worldwide which is gaining importance in India as well. Circle hooks are getting more popular as it shows less injury with enhanced post-release survival, which promote catch and release as well as conservation. In the present study, circle and ‘J’ hooks were compared for hooking pattern, extent of injury and post-release survival in Genetically Improved Farmed Tilapia (GIFT) in recreational fishing. Results depicted that overall hooking rate was lower for circle hooks (29%) than ‘J’ hooks (31%). Occurrence of lip hooking was more with circle hooks (73.6%) than ‘J’ hooks (58.8%), whereas jaw hooking was comparatively low in case of circle hooks than ‘J’ hooks. Circle hooks showed no throat hooking whereas ‘J’ hooks recorded 5.88% for the same. Foul hooking was not observed in case of both hook types. In the present study, with ‘J’ hooks, 52.9% of fishes showed no bleeding, slight and moderate bleeding was found in 17.6% fishes, whereas 11.7% had severe bleeding. For circle hooks, the corresponding values were 73.6, 21.05, 5.26 and 0%. There was 100% survival for the fishes upto 72 h post-release in both cases. Keywords: Circle hook, Hooking pattern, ‘J’ hook, Recreational fisheries, Tilapia